Rules of Preference in the Qur’ānic Commentary of Qāḍī Thanā Allāh Pānīpatī - Farwa, Ume (الدراسات الإسلامية, 2020)
This paper aims to study and analyze the principles of preferences in interpretation of the Qur’ān, as applied by Qāḍī Thanā’Allāh Pānīpatī (d. 1810) in his famous commentary known as Al-Tafsīral-Maẓharī. He was one of the most eminent scholars of the Qur’ānic exegesis in the Indian subcontinent. He was descended from the third caliph ‘Uthmān b ‘Affān and hailed from the historic city Pānīpat, Haryana, India. He got his early education in his native village and travelled to Delhi for higher education. In this research work, I have explained seven principles on which Qāḍī Thanā’Allāh has mostly relied in his commentary in addition to different opinions of the Qur’ānic commentators. The method of preference along with established rules applied by Qāḍī Thanā’Allāh has been discussed in this article in order to highlight his contribution to the Qur’ānic exegesis with respect to the principles of preference. Keywords: Principles, Preferences, Qāḍī, Thanā’Allāh, Pānīpatī, Interpretation, Qur’ānic Exegesis, Al-Tafsīral-Maẓharī.